tính
5/6:8/3=
3/5:10=
14x5/21=
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1-2-3+4+5-6-7+8+9-10-...+20-21\)
\(=\left(1-2-3+4\right)+\left(5-6-7+8\right)+....+\left(17-18-19+20\right)-21\)
\(=0+0+...+0-21\)
\(=-21\)
a)
\(\dfrac{-5}{21}+\left(\dfrac{-16}{21}+1\right)=\dfrac{-5}{21}+\dfrac{-16}{21}+1\)=\(-1+1=0\)
`(-5)/21+((-16)/21+1)`
`=(-5)/21-16/21+1`
`=-1+1=0`
`(-3)/8*1/6+3/(-8)*5/6+(-1)/16`
`=-3/8*(1/6+5/6)-10/16`
`=-3/8-10/16`
`=-6/16-10/16=-16/16=-1`
1: \(=\dfrac{272-168+186}{30}\cdot\dfrac{7}{9}=\dfrac{29}{3}\cdot\dfrac{7}{9}=\dfrac{203}{27}\)
2: \(=\dfrac{9-55}{33}\cdot\dfrac{6-5}{8}-\dfrac{4}{5}\cdot\dfrac{1}{24}=\dfrac{-4}{3}\cdot\dfrac{1}{8}-\dfrac{1}{30}=\dfrac{-1}{6}-\dfrac{1}{30}=\dfrac{-6}{30}=-\dfrac{1}{5}\)
3: \(=\dfrac{7}{3}\left(\dfrac{6}{25}+\dfrac{19}{25}\right)=\dfrac{7}{3}\cdot1=\dfrac{7}{3}\)
A = ( 6 : 3/5 - 7/6 x 6/7 ) : ( 21/58 x 10/11 + 57/11 )
A = 9 : .....
A = .......
5/9x12/7=20/21
6/5:8/3=9/20
9/20x5/12=3/16
15/16:25/24=9/10
14x5/21=10/3
10:5/3=6
5/3:10=1/6
5/9 x 12/7 = 60/63
6/5 : 8/3 = 6/5 x 3/8 = 9/20
9/20 x 5/12 = 3/16
15/16 : 25/24 = 15/16 x 24/25 = 9/10
14 x 5/21 = 60/21
10 : 5/3 = 10 x 3/5 = 6
5/3 : 10 = 5/3 x 1/10 = 1/6
a) Ta có: \(\dfrac{-5}{7}\left(\dfrac{14}{5}-\dfrac{7}{10}\right):\left|-\dfrac{2}{3}\right|-\dfrac{3}{4}\left(\dfrac{8}{9}+\dfrac{16}{3}\right)+\dfrac{10}{3}\left(\dfrac{1}{3}+\dfrac{1}{5}\right)\)
\(=\dfrac{-5}{7}\cdot\dfrac{3}{2}\cdot\dfrac{21}{10}-\dfrac{3}{4}\cdot\dfrac{56}{3}+\dfrac{10}{3}\cdot\dfrac{8}{15}\)
\(=\dfrac{-9}{4}-14+\dfrac{16}{9}\)
\(=\dfrac{-1621}{126}\)
b) Ta có: \(\dfrac{17}{-26}\cdot\left(\dfrac{1}{6}-\dfrac{5}{3}\right):\dfrac{17}{13}-\dfrac{20}{3}\left(\dfrac{2}{5}-\dfrac{1}{4}\right)+\dfrac{2}{3}\left(\dfrac{6}{5}-\dfrac{9}{2}\right)\)
\(=\dfrac{-17}{26}\cdot\dfrac{13}{17}\cdot\dfrac{-3}{2}-\dfrac{20}{3}\cdot\dfrac{3}{20}+\dfrac{2}{3}\cdot\dfrac{-33}{10}\)
\(=\dfrac{3}{4}-1-\dfrac{11}{5}\)
\(=-\dfrac{49}{20}\)
\(\dfrac{5}{6}:\dfrac{8}{3}=\dfrac{5}{6}\)x\(\dfrac{3}{8}=\dfrac{15}{48}=\dfrac{5}{16}\)
\(\dfrac{3}{5}:10=\dfrac{3}{5}:\dfrac{10}{1}=\dfrac{3}{5}\)x\(\dfrac{1}{10}\)\(=\dfrac{3}{50}\)
\(14\)x\(\dfrac{5}{21}=\dfrac{14}{1}\)x\(\dfrac{5}{21}=\dfrac{70}{21}=\dfrac{10}{3}\)